2022
DOI: 10.3390/soc12010011
|View full text |Cite
|
Sign up to set email alerts
|

‘Health in All Policies’ and the Urge for Coordination: The Work of Public Health Coordinators and Their Impact and Influence in Local Public Health Policies: A Cross-Sectional Study

Abstract: Building heavily on the Health in All Policies (HiAP) approach, Norway implemented the Public Health Act in 2012 to reduce social inequalities in health. Local public health coordinators (PHCs) at municipal levels were seen as tools to provide local intersectoral public health work. In this study, we examine factors related to intersectoral agency and if intersectoral work is understood as relevant to securing social justice in local policy outcomes. A national web-based survey in 2019 of all Norwegian PHCs (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
3
0
2
Order By: Relevance
“…The main factor in the successful coordination of the public health response is the governors' ability to support the municipalities and the local communities, balancing the need for independence against the need for state control. Karlsen et al (2022) highlighted that municipal public health coordinators (PHCs) are an important 'tool' for providing local intersectoral public health work. The founders of the social services facilities are the municipalities, and thus, the ability of the governors to coordinate work on measures against the spreading of the pandemic had a direct impact on the protection of those placed in these facilities.…”
Section: Discussionmentioning
confidence: 99%
“…The main factor in the successful coordination of the public health response is the governors' ability to support the municipalities and the local communities, balancing the need for independence against the need for state control. Karlsen et al (2022) highlighted that municipal public health coordinators (PHCs) are an important 'tool' for providing local intersectoral public health work. The founders of the social services facilities are the municipalities, and thus, the ability of the governors to coordinate work on measures against the spreading of the pandemic had a direct impact on the protection of those placed in these facilities.…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that public health work in the municipalities is largely rooted in the municipality health and care services and that public health work appears to be health sector‐oriented 43 . Another study carried out by Melby and Mandal 53 of the role of nurses in public health work reinforces this impression.…”
Section: How the Practice Of Hiap Deals With The Dilemmasmentioning
confidence: 98%
“…Karlsen et. al 43 also found the municipal health coordinators can be important tools in affecting local public health policies.…”
Section: How the Practice Of Hiap Deals With The Dilemmasmentioning
confidence: 99%
“…For kommunelegefunksjonen generelt er det funnet at stillingsstørrelse synes å vaere en viktig faktor i mindre kommuner (9). I studier av folkehelsekoordinatorene har man funnet at stillingsstørrelse og naerhet til beslutningstakere virker inn på deres evne til å påvirke og fungere som brobyggere (29). Til tross for at det er 12 år siden innføringen av folkehelseloven, finnes det få studier om kommunelegens rolle i folkehelsearbeidet i Norge.…”
Section: Kommunelegen I Folkehelsearbeidetunclassified
“…Det utløser et behov for integrasjon ved å bringe sammen tidligere spredte og uavhengige tjenester til et mer helhetlig leveransesystem (37,38). For kommunelegen betyr dette en utvikling fra å vaere relativt selvgående til å vaere en etterspurt partner i folkehelsearbeidet, også fordi de fortsatt er en aktør som kan gi arbeidet økt gjennomslagskraft (29).…”
Section: Kommunelegen Som øNsket Ressurs I Folkehelsearbeidetunclassified